Anatomical distribution of cerebral microbleeds and intracerebral hemorrhage in vertebrobasilar dolichoectasia - Förster, Alex; Maros, Máté E.; Böhme, Johannes; Al-Zghloul, Mansour; Alonso, Angelika; Groden, Christoph; Wenz, Holger (PLOS ONE, 2018)
Objectives Vertebrobasilar dolichoectasia (VBD) is a dilatative arteriopathy associated with intracerebral hemorrhage. In the present study, we sought to evaluate the frequency and anatomical distribution of cerebral microbleeds (cMBs) and intracerebral hemorrhage (ICH) in VBD. Methods From a MRI database 94 VBD patients were identified and analyzed with special emphasis on cMBs and ICH on T2*-weighted gradient echo images (GRE) in relation to the established diagnostic MRI criteria of VBD (diameter, height, and lateral position). cMBs/ICH location was categorized into anterior/posterior circulation. Clinical information like demographic details, clinical symptoms, and comorbidities were abstracted from the case records. An extensive modelling approach using generalized linear mixed-effects models was used. Results Overall, 79 (84.0%) patients (mean age 72.1±10.0 years, 74.7% male) with a standard stroke MRI protocol including T2*-weighted images were included in the analysis. cMBs were observed in 38/79 (48.1%) patients, ranging from 1 to 84 cMBs per patient. In the posterior circulation cMBs were observed more frequently (34/38 (89.5%)) in comparison to the anterior circulation (24/38 (63.2%)). cMBs were observed in the thalamus in 20/38 (52.6%), hippocampus in 1/38 (2.6%), occipital lobe in 18/38 (47.4%), pons in 6/38 (15.8%), medulla oblongata in 2/38 (5.2%), and cerebellum in 14/38 (36.8%) patients. ICH was observed in only 6/79 (7.6%) patients. There were significantly more cMBs in the posterior- (NCMBs-PC = 1.717, 95%CI: 1.336-2.208, p = 0.0315) than in the anterior circulation. Logistic regression model showed a significant positive effect of clinical symptoms such as ischemic, TIA and hemorrhagic stroke on the presence of cMBs (OR = 3.34, 95%CI [2.0-5.57], p = 0.0184; ndf = 78, AIC = 107.51). General linear model showed that clinical symptoms have a highly significant effect on the number of cMBs (N = 2.78, 95%CI [2.51-3.07], p<2*10-16; ndf = 78, AIC = 1218). Conclusion cMBs and ICH may be observed in the anterior and posterior circulation in VBD but they occur more frequently in the posterior circulation. Most common anatomical locations of cMBs in VBD were the thalamus, occipital lobe and cerebellum. This posterior dominance of cMBs and ICH in VBD might reflect a specific underlying vascular pathology.
Gesehen am 13.08.2020